A Low-Pass Filter of Wide Stopband with a Novel Multilayer Fractal Photonic Bandgap Structure - Hai-Wen Liu; Xiao-Wei Sun; Zheng-Fan Li (Active and Passive Electronic Components)
A novel, multilayer fractal PBG is presented here as the substrate for a microstrip line and the resulting configuration builds a low-pass filter of wide stopband. Experimental results in comparison with the corresponding two filters with monolayer PBG show that the proposed filter drastically enhances the width of the stopband.